2018
DOI: 10.3390/data3020011
|View full text |Cite
|
Sign up to set email alerts
|

SIMADL: Simulated Activities of Daily Living Dataset

Abstract: With the realisation of the Internet of Things (IoT) paradigm, the analysis of the Activities of Daily Living (ADLs), in a smart home environment, is becoming an active research domain. The existence of representative datasets is a key requirement to advance the research in smart home design. Such datasets are an integral part of the visualisation of new smart home concepts as well as the validation and evaluation of emerging machine learning models. Machine learning techniques that can learn ADLs from sensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…This section presents the evaluation methodology for analyzing the efficacy of the ZASH system. We implemented and executed the ZASH system with Python 3.9.5 in Zorin OS 15.3 using SIMADL (Simulated Activities of Daily Living Dataset) [Alshammari et al 2018] and can be found at GitHub 1 . The technology was chosen for its portability, ease of file manipulation and ease of algorithms writing, providing quick development and evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…This section presents the evaluation methodology for analyzing the efficacy of the ZASH system. We implemented and executed the ZASH system with Python 3.9.5 in Zorin OS 15.3 using SIMADL (Simulated Activities of Daily Living Dataset) [Alshammari et al 2018] and can be found at GitHub 1 . The technology was chosen for its portability, ease of file manipulation and ease of algorithms writing, providing quick development and evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Zerkouk and Chikhaoui [ 27 ] proposed a method based on LSTM to estimate older people's abnormal behaviors. They used SIMADL [ 28 ] dataset in their experiments. A novel symptom-based “Unified Parkinson Disease Rating Scale” estimation system was presented by Hssayeni et al [ 14 ].…”
Section: Related Studiesmentioning
confidence: 99%
“…An autoencoder [32] is a multi-layer neural network in which the desired output is the input itself. The aim of autoencoder is to learn more advanced feature representation in compressed representation to catch the most significant features of the training data [33].…”
Section: Autoencoder-cnn-lstmmentioning
confidence: 99%